THE EFFECTIVENESS OF ELSA SPEAK FOR FIRST-SEMESTER EFL STUDENTS - Dadan Hidayat; Chodidjah Chodidjah; Rina Lestari; Kalsum Kalsum (Al-Irsyad: Journal of Education Science, 2026)
This study investigated the effectiveness of the ELSA Speak application in improving the speaking ability of first-semester EFL students. Many beginner learners still face difficulties in speaking English, especially in pronunciation, fluency, vocabulary use, and confidence during oral communication. To address these problems, ELSA Speak provides AI-supported speaking exercises, pronunciation feedback, and repeated practice that allow students to learn independently in a flexible environment. The research applied a pre-experimental method using a one-group pre-test and post-test design. The participants were 25 first-semester English students who attended eight treatment sessions over four weeks. Students’ speaking performance was evaluated through several aspects, including pronunciation, fluency, vocabulary, and confidence. The findings showed that students’ speaking scores improved after using the application. The average score increased from 56.12 in the pre-test to 78.36 in the post-test. In addition, the paired-sample t-test indicated a statistically significant improvement (t(24) = 20.31, p < .001). The study suggests that the ELSA Speak application may support speaking development by providing interactive and motivating speaking practice. Furthermore, AI-based mobile learning applications can serve as supportive tools in technology-assisted language learning for EFL students.